Pengaruh Viral Marketing, E-Wom, dan Label Halal terhadap Keputusan Pembelian Produk Mixue di Kalangan Pengikut Instagram @Mixueindonesia di Jabodetabek - Shopia Dwi Lestari; Ditiya Himawati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the influence of Viral Marketing, Electronic Word of Mouth (E-WoM), and Halal Label on the purchase decision of Mixue products among Instagram followers of @Mixueindonesia in the Jabodetabek area. This research uses a quantitative approach with primary data collected through questionnaires distributed to 140 respondents. Data analysis was conducted using multiple linear regression, including validity and reliability tests, classical assumption tests, t-test, F-test, and coefficient of determination. The results show that Viral Marketing has a positive effect on purchase decisions with a t-value of 3.430 and a significance level of 0.001. E-WoM also has a positive and significant effect on purchase decisions with a t-value of 3.910 and a significance level of 0.002. Meanwhile, the Halal Label variable has a t-value of 2.010 with a significance level of 0.0458, but it is not considered to have an effect on purchase decisions in this study. Simultaneously, Viral Marketing, E-WoM, and Halal Label significantly influence purchase decisions, as indicated by an F-value of 215.891 and an adjusted R-square of 0.652. These findings indicate that digital marketing strategies and consumer-to-consumer communication play a more dominant role than halal labeling in shaping purchase decisions for Mixue products.